The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1984
DOI: 10.1002/eji.1830140414
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐protection in mice infected with influenza A virus by the respiratory route is correlated with local IgA antibody rather than serum antibody or cytotoxic T cell reactivity

Abstract: Mice previously infected with an aerosol of A/Rec 31 influenza virus were strongly protected against an aerosol challenge with A/Vic influenza as judged by lung virus titers recovered 2 days after the challenge infection. Such complete homotypic immunity was not achieved by priming with live Rec 31 virus injected i.v. or UV-inactivated Rec 31 virus administered s.c. together with Al(OH)3 and saponin. The reason for the superior protective effect of the natural infection was investigated. The protection induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
153
0
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(161 citation statements)
references
References 35 publications
1
153
0
2
Order By: Relevance
“…values for IgA in the BALF, further suggesting the importance of cross-reactive IgA for Het-I at the respiratory mucosa. In mice, cross-reactive IgA induced by natural infection was shown to be strongly correlated to protection from challenge with a heterologous homotypic virus [35]. Serum HI antibody titer and cross-reactive cytotoxic T-lymphocytes were not correlated with protection from infection, but instead were related to recovery [35].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…values for IgA in the BALF, further suggesting the importance of cross-reactive IgA for Het-I at the respiratory mucosa. In mice, cross-reactive IgA induced by natural infection was shown to be strongly correlated to protection from challenge with a heterologous homotypic virus [35]. Serum HI antibody titer and cross-reactive cytotoxic T-lymphocytes were not correlated with protection from infection, but instead were related to recovery [35].…”
Section: Discussionmentioning
confidence: 98%
“…Virus was not detected from any pigs in this group at any time point and macroscopic and microscopic lesions were both significantly reduced to minimal or undetectable levels. Live challenge and recovery or natural exposure to influenza virus has been well documented to have improved Het-I over inactivated vaccines [35][36][37][38]. To demonstrate the ability of the NS1 deletion mutant in inducing Het-I, vaccinated pigs were challenged with a heterologous H3N2 and a heterosubtypic rH1N1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been demonstrated in the mouse model that passive transfer of immunoglobulins protect against challenge with infectious influenza virus (Virelizier et al, 1976(Virelizier et al, , 1979. In addition the study of immunoglobulin isotypes stimulated by the inoculation of different virus preparations (Liew et al, 1984) has attempted to examine the antibody isotype involved in these protection mechanisms (Balkovic et al, 1987). With its widespread occurrence in the bloodstream, lymphatics and peripheral body fluids the antibody isotype IgG is likely to be the most important in neutralizing the virus (Possee et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Foster nursing can confer homosubtypic protection, supporting a role for secretory IgA (14). Some reports have suggested that IgA in secretions may be more cross-reactive than IgG (15)(16)(17)(18)(19); such cross-reactivity may be a mechanism through which IgA could contribute to heterosubtypic immunity. Interference with viral replication or assembly during transcytosis (20,21), as suggested for rotavirus (22), is a potential mechanism that might be mediated by IgA Abs to conserved internal proteins.…”
mentioning
confidence: 99%